2013
DOI: 10.1111/aogs.12186
|View full text |Cite
|
Sign up to set email alerts
|

The experience of pregnant women with a body mass index >30 kg/m2 of their encounters with healthcare professionals

Abstract: Pregnant women with obesity may experience prejudice from healthcare professionals. These women felt they were treated with a lack of respect, an accusatorial response, and the feeling that information which could have been helpful was not forthcoming. Communication between obese pregnant woman and healthcare professionals appears to be lacking. Improved training in communication skills, less judgemental behaviour and better dissemination of information from healthcare professionals working with pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 22 publications
4
83
1
1
Order By: Relevance
“…Overweight male patients perceived poorer quality of care from physicians, including reduced length of consultation (Hebl et al, 2003). Pregnant women with a BMI greater than 30 kg/m 2 reported accusatory responses, a lack of respect and insufficient helpful advice from their general practitioners (Lindhardt et al, 2013). Patients who perceived negative judgement about their weight trusted their health professionals less than those who did not (Gudzune et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Overweight male patients perceived poorer quality of care from physicians, including reduced length of consultation (Hebl et al, 2003). Pregnant women with a BMI greater than 30 kg/m 2 reported accusatory responses, a lack of respect and insufficient helpful advice from their general practitioners (Lindhardt et al, 2013). Patients who perceived negative judgement about their weight trusted their health professionals less than those who did not (Gudzune et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Being categorized as a group with a disease may increase the risk of exclusion and stigmatization of vulnerable groups (National Institute for Public Health, 2007: p. 264). Recent empirical studies show that individuals with obesity in general, and pregnant women with obesity in particular, have a higher prevalence of depression, feelings of low self-esteem and stigmatization in their encounters with healthcare professionals (Lindhardt et al, 2013;Malterud & Ulriksen, 2011). Stigmatization in general creates a gap in social identity, selfawareness and perception by others (Goffman, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…Overweight pregnant women characterize the medical profession's approach to them as lacking respect, engaging in moral condemnation and withholding important information (Lindhardt, Rubak, Mogensen, Lamont, & Joergensen, 2013: p. 1101. Furthermore, in the experience of overweight pregnant women, persons in power do not always recognize the degrading attitudes and behaviour that these women face in health care (Malterud & Ulriksen, 2011: p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have reported similar results. For example, a Danish study using a phenomenological approach found that pregnant women with a BMI above 30 felt that they received accusatory responses and judgement in conversations with general practitioners (Lindhardt, Rubak, Mogensen, Lamont, & Joergensen, 2013).…”
Section: Chapter 5: Patient Perceptions Of Weight-related Interactionmentioning
confidence: 99%
“…Overweight male patients perceived poorer quality of care from physicians, including reduced length of consultation (Hebl et al, 2003). Pregnant women with a BMI greater than 30kg/m 2 reported accusatory responses, a lack of respect and insufficient helpful advice from their general practitioners (Lindhardt et al, 2013). Patients who perceived negative judgment about their weight trusted their health professionals less than those who did not .…”
Section: Chapter 5: Patient Perceptions Of Weight-related Interactionmentioning
confidence: 99%